EFEKTIVITAS PEMBERIAN JAMU TRADISIONAL GEPYOKAN TERHADAP KELANCARAN ASI PADA IBU NIFAS DI WILAYAH KERJA PUSKESMAS SIKUI - Wismawati, Wismawati; Rahmawati, Dwi; Mardiatul Ulfa, Ika; Widiya Ningrum, Novalia (LPPM Universitas Sari Mulia, 2024)
Background: Children who are breastfed have higher intelligence test results. In addition, they have a lower chance of being obese or overweight. Puskesmas Sikui ranks 5th for the achievement of Exclusive Breastfeeding. During the postpartum and lactation period, people consume a lot of herbs, because they believe that herbal medicine can launch breast milk, one of which is the traditional gepyokan herbal medicine consisting of ginger, turmeric kencur, temulawak and katuk leaves. The content in it has various properties and is natural without preservatives and chemicals that can damage the health of the body. Objective: Knowing the effectiveness of giving Gepyokan traditional herbal medicine to smooth breast milk for postpartum mothers in the working area of the Sikui Health Center Method : Research Method using Pre Experiment with One Group Pretest-Posttest design. The sampling technique is determined based on purposive sampling. Results : Univariate results, pretest 9 (90%) of 10 respondents breastfeeding is not smooth. 1 (10%) breast milk is smooth. 9 (90%) respondents consume herbal medicine regularly, 1 (10%) respondents do not regularly consume herbal medicine. Posttest results 9 (90%) respondents breastfed smoothly and 1 (10%) breast milk is not smooth. Bivariate results, normality test using Shapiro-wilk abnormal data results. Then an alternative test using Wilcoxon, the result of H0 is rejected and Ha is accepted. Conclusion : Gepyokan traditional herbal medicine can launch breast milk for postpartum mothers in the Sikui Health Center Working Area. Keywords: puerperal mother, gepyokan traditional jamu, smooth breastfeeding